Double butterfly theorem on ellips - Mashadi, Mashadi; Dinata, Muhammad Farhan (Hilbert Journal of Mathematical Analysis, 2022)
The butterfly and the double butterfly theorem are applied to a circle. In this paper, we will modify the double butterfly theorem on an ellipse. The method of proving the double butterfly theorem on an ellipse can be done if Haruki’s lemma can apply to any ellipse. Thus, in this paper will also be given a modified Haruki’s lemma on an ellipse.